Pelaksanaan Pemeliharaan Kerukunan Umat Beragama kaitannya dengan Qanun Aceh Pasal 9 Ayat 1 Tahun 2015 - Mawardi Mawardi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Abstract: Social diversities in a nation state is inevitable due to knowledge, sensory, intelligent and communication barriers. In social interaction, this limitation creates groupings in a society known as identity. Unfortunately, constellation among identities not only produced collaboration but often resulted in violence and casualties. This unfavorable constellation generally takes place in the transition period during which the country is still concentrating on improving its mechanisms towards a fair, transparent and open democratic system. The maintenance of religious harmony in Aceh is regulated in Aceh Qanun, Article 9, paragraph 1 of 2015. This article aims to describe the implementation of religious harmony in its connection with the article. The local Government has done three measures to maintain religious harmonies such as the establishment of FKUB  (Forum for Religious Harmony) and its Advisory Board and Understanding and Socialization of Joint Regulation of the Ministry of Religion and Ministry of Interior No. 9 of 2006 / No. 8 of 2006 Abstrak: Dalam kehidupan berbangsa dan bernegara, keragaman memiliki akar mendalam berdasarkan keterbatasan pada pengetahuan, penginderaan, akal dan komunikasi bahasa. Keterbatasan ini dalam interaksi sosial melahirkan pengelompokan-pengelompokan dalam masyarakat sebagai identitas. Sayangnya konstelasi antar identitas tidak hanya melahirkan kerjasama tetapi seringkali berbuntut kekerasan dan menelan korban. Konstelasi yang tidak menguntungkan ini umumnya dalam masa transisi, negara masih berkonsentrasi memperbaiki mekanisme menuju sistem demokrasi yang adil, transparan dan terbuka. Dalam pemeliharaan kerukunan umat beragama, Aceh berpedoman pada Qanun Aceh pasal 9 Ayat 1 tahun 2015. Artikel ini mencoba mendeskripsikan pelaksanaan pemeliharaan kerukunan umat beragama dalam kaitan dengan pasal tersebut di atas. Untuk mewujudkan pemeliharaan kerukunan umat beragama Pemerintah Aceh sudah melaksanakan tiga langkah, meliputi pembentukan Forum Kerukunan Umat Beragama (FORKUB/FKUB), pembentukan Dewan Penasehat Forum Kerukunan Umat Beragama dan Pemahaman serta Sosialisasi Peraturan Bersama Menteri Agama dan Menteri Dalam Negeri Nomor 9 Tahun 2006/ Nomor 8 Tahun 2006.